Strategic Model for Process Management in an SME in the Commercial Sector in Trujillo - Suarez Torres, Betty Lizby; Araujo Casanova, Kimberlin Liseth (LACCEI, 2024)
The objective of this research is to determine the influence of the implementation of a strategic model in process management in a microenterprise in the commercial sector of Trujillo, which is dedicated to the sale of essential products. The research has a pre-experimental and cross-sectional design, a sample population of 32 registered clients was considered; In addition, instruments such as summary sheets, observation guide and questionnaire with open questions were used for the collection of data and information. A survey was also used, which was validated through expert judgment and reliability was verified using Cronbach’s Alpha, obtaining a result of 0.835. After the implementation of the model based on D’Alessio, the proposed strategies were evaluated, obtaining as results those complaints decreased by 63%, customer satisfaction increased 50% with respect to the product and 55.21% with respect to the service, likewise Sales increased by 27.82%, employee satisfaction increased by 33.33%. The conclusion shows that the strategic model positively influences the microenterprise, obtaining a profitable economic evaluation with a NPV of S/ 10791.54, IRR of 41% and B/C=1.21, which means that it is viable